1993
DOI: 10.1080/07448481.1993.9936324
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Sexual Risk Behaviors among College Students following a Comprehensive Health Education Intervention

Abstract: Sexually active college students are at risk of contracting sexually transmitted diseases, including HIV infection. As a result, health education initiatives to prevent these infections are commonplace, but few controlled research studies have evaluated behavioral changes as a result of on-campus sex education. In a nonrandomized control trial, sexual risk behaviors of 341 students who had received a comprehensive health education intervention in a first-year seminar were compared with 227 students who were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…In some studies examining the rate of condom use among college students, males have reported more consistent condom use than females (e.g., Bazargan, Kelly, Stein, Husaini, & Bazargan, 2000;Winfield & Whaley, 2002), but in other studies no such gender difference has been found (e.g., Hawkins, Gray, & Hawkins, 1995). Some studies have found a greater tendency for women to reduce their number of sexual partners as a risk reduction strategy (e.g., Hawkins, Gray, & Hawkins, 1995), whereas other studies have failed to find this difference (e.g., O'Leary et al, 1996;Turner et al, 1993). In this study, we hypothesized that men would report higher rates of condom use, largely because of the additional burden on women of having to persuade their male sexual partners to use condoms.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In some studies examining the rate of condom use among college students, males have reported more consistent condom use than females (e.g., Bazargan, Kelly, Stein, Husaini, & Bazargan, 2000;Winfield & Whaley, 2002), but in other studies no such gender difference has been found (e.g., Hawkins, Gray, & Hawkins, 1995). Some studies have found a greater tendency for women to reduce their number of sexual partners as a risk reduction strategy (e.g., Hawkins, Gray, & Hawkins, 1995), whereas other studies have failed to find this difference (e.g., O'Leary et al, 1996;Turner et al, 1993). In this study, we hypothesized that men would report higher rates of condom use, largely because of the additional burden on women of having to persuade their male sexual partners to use condoms.…”
mentioning
confidence: 93%
“…The sexual experimentation, partner change, peer influence, and use of alcohol and drugs characteristic of young adults in their late teens and 20s have made college students potentially vulnerable to infection (MacDonald et al, 1990). For this reason, college students have been the subjects of empirically tested HIV prevention interventions using educational strategies (e.g., O'Leary, Jemmott, Goodhart, & Gebelt, 1996;Turner et al, 1994;Turner, Korpita, Mohn, & Hill, 1993) and skills training in condom use, assertiveness, and communication (e.g., Basen-Engquist, 1994;Bryan, Aiken, & West, 1996;Franzini, Sideman, Dexter, & Elder, 1990;Sikkema, Winett, & Lombard, 1995).…”
mentioning
confidence: 98%
“…As with HIV prevention interventions in other populations, college interventions typically target the HIV-related knowledge, attitudes, and behaviors of participants (Basen-Engquist, 1994; Chernoff & Davison, 2005; Swanson et al , 1999; Turner et al , 1994; Turner et al , 1993). Interventions aim to modify the knowledge and attitudes that shape behavioral intentions and behaviors themselves.…”
Section: Effective Hiv Preventionmentioning
confidence: 99%
“…2000). The content of such programmes has focused on knowledge of STD or HIV, safer sex techniques, contraceptive methods, communication skills and self‐efficacy (Jemmott et al . 1992, 1993, Kasen et al 1992, Turner et al 1993, Kirby et al .…”
Section: Introductionmentioning
confidence: 99%